Treatment of endovenous heat-induced thrombosis (EHIT) with rivaroxaban (Xarelto®) - Werth, S.; Halbritter, K.; Mahlmann, A.; Weiss, N. (Phlebologie, 2015)
Introduction: Endovenous heat-induced thrombosis (EHIT) is a known complication after endovenous ablation of the superficial varicose veins (incidence rate 0–6 % (varies by definition and diagnostic algorithm). However, only expert suggestions for indication, duration and dosing of treatment drugs exist. The most common recommendation is low-molecular weight heparin in half-therapeutic dosage for EHIT class 2 and therapeutic dosage for patients with EHIT class 3 or 4. Rivaroxaban is an attractive option in the treatment of venous thromboembolic diseases due to the simplification of treatment.Case report: After successful ablation of the great saphenous vein (GSV) in a patient with complete insufficiency (Hach III) combined with sclerotherapy of superificial varicose veins of the calf the patient got a prophylactic anticoagulation with low-molecular weight heparin (LMWH) and compressions stockings grade II. Nevertheless we saw in the control-compression ultrasound after 7 days an asymptomatic EHIT class 1. Due the progression to EHIT class 3 after another seven days under watchful waiting we treated the patient with Rivaroxaban for 14 days. After the treatment we saw a complete resolution of the clot. Anticoagulant treatment and compression stockings (for three weeks after EVLT) were discontinued.
Keywords: EHIT; thrombosis; endovenous; rivaroxaban